Corporate Social Responsibility Development and Climate Change: Regional Evidence of China - Shouhao Li (MDPI AG, 2021)
This study analyzed Chinese companies’ behavior regarding corporate social responsibility (CSR) disclosure, and its impact on national and regional climate change measured by carbon emissions. CSR disclosure, supported by existing theories, is considered a powerful tool to curb climate change issues. We combined data of companies’ publicly traded annual financial reports and CSR reports from the China Stock Market and Accounting Research (CSMAR) database and provincial macroeconomic statistics from the Chinese National Bureau of Statistics to run panel regressions. The results verify the following: (a) China is in a relatively early stage of CSR development, and Chinese firms’ internal incentives to adopt CSR projects are low since none of the internal factors researched contribute to CSR disclosure. (b) External factors work slightly better for CSR practices, but at the same time, the CSR regulations still need further improvement. (c) The current CSR disclosure practices do not have a clear impact on carbon emission reduction, contrary to some predictions that CSR could help reduce carbon emissions.